Physical Activity Might Reduce the Adverse Impacts of the FTO Gene Variant rs3751812 on the Body Mass Index of Adults in Taiwan - Liaw, Yi-Ching (Genes (Basel), 2019)
The fat mass and obesity-associated (FTO) gene is a significant genetic contributor to polygenic obesity. We investigated whether physical activity (PA) modulates the effect of FTO rs3751812 on body mass index (BMI) among Taiwanese adults. Analytic samples included 10,853 Taiwan biobank participants. Association of the single-nucleotide polymorphism (SNP) with BMI was assessed using linear regression models. Physical activity was defined as any kind of exercise lasting 30 min each session, at least three times a week. Participants with heterozygous (TG) and homozygous (TT) genotypes had higher BMI compared to those with wild-type (GG) genotypes. The β value was 0.381(p < 0.0001) for TG individuals and 0.684 (p = 0.0204) for TT individuals. There was a significant dose-response effect among carriers of different risk alleles (p trend <0.0001). Active individuals had lower BMI than their inactive counterparts (β = −0.389, p < 0.0001). Among the active individuals, significant associations were found only with the TG genotype (β = 0.360, p = 0.0032). Inactive individuals with TG and TT genotypes had increased levels of BMI compared to those with GG genotypes: Their β values were 0.381 (p = 0.0021) and 0.950 (p = 0.0188), respectively. There was an interaction between the three genotypes, physical inactivity, and BMI (p trend  = 0.0002). Our data indicated that increased BMI owing to genetic susceptibility by FTO rs3751812 may be reduced by physical activity.